The Influence of Transformational Leadership Style and Discipline on The Performance of Village Apparatus Is Mediated by Job Satisfaction in Villages Serang Baru Sub-District, Bekasi Regency - Aming; Supriyanto; Setyaningrum, Retno Purwani (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to analyze the influence of Transformational Leadership Style and Discipline on Village Apparatus Performance mediated by Job Satisfaction in the villages of Serang Baru Subdistrict, Bekasi Regency. Data were collected through questionnaires and analyzed using the Smart PLS application. The results indicate that Transformational Leadership Style does not significantly affect Village Apparatus Performance or Job Satisfaction. Conversely, Discipline has a significant positive effect on both Village Apparatus Performance and Job Satisfaction. Additionally, Job Satisfaction has a significant positive effect on Village Apparatus Performance. Job Satisfaction does not mediate the relationship between Transformational Leadership Style and Performance but significantly mediates the relationship between Discipline and Performance. The implications of this study highlight the importance of developing work discipline and job satisfaction to enhance the performance of village apparatus. Future researchers are advised to explore other leadership styles, consider contextual and cultural factors, use different methodologies, conduct longitudinal studies, and investigate other moderating and mediating factors to gain a more comprehensive understanding.